2018
DOI: 10.1097/pcc.0000000000001545
|View full text |Cite
|
Sign up to set email alerts
|

Do-Not-Resuscitate Orders in the Neonatal ICU: Experiences and Beliefs Among Staff*

Abstract: Most neonatal ICU staff report experience with do-not-resuscitate orders; however, many, particularly nurses and respiratory therapists, report no training in this area. Variable beliefs with respect to withholding and withdrawing care for patients with do-not-resuscitate orders exist among staff. Because neonatal ICU patients with do-not-resuscitate orders may ultimately survive, withholding or withdrawing interventions may have long-lasting effects, which may or may not coincide with familial intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
2
0
5
Order By: Relevance
“…Needs include emotional support for staff members, formalized palliative care teams, concrete guidelines for the administration of neonatal palliative care, and further education. 5,6,8,16,18,24,25 The emotional toll that caring for dying infants takes on providers is substantial, and impacts all providers. Providers report feeling sadness and grief, as well as professional inadequacy, meaning that they feel they did not do enough for the infant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Needs include emotional support for staff members, formalized palliative care teams, concrete guidelines for the administration of neonatal palliative care, and further education. 5,6,8,16,18,24,25 The emotional toll that caring for dying infants takes on providers is substantial, and impacts all providers. Providers report feeling sadness and grief, as well as professional inadequacy, meaning that they feel they did not do enough for the infant.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies investigated the experiences of staff members with do-not-resuscitate (DNR) orders for neonates and found that the majority of staff did not understand the legal meaning of a DNR status and varied in their interpretation of the status. 16,25…”
Section: Resultsmentioning
confidence: 99%
“…Merjenje moči dokazov vključenih člankov smo določili po Polit & Beck (2018), ki navajata osem nivojev hierarhije dokazov v znanstvenoraziskovalnih delih. V nivo 5 -dokazi retrospektivnih raziskav primerov s kontrolami -smo uvrstili dve enoti literature (Arzuaga et al, 2018;Bremer et al, 2021). V nivo 6 -dokazi presečnih raziskav -smo uvrstili dvanajst enot literature (Khalaileh, 2014;Mogadasian et al, 2014;Ilsar, 2015;O'Brien et al, 2018;Pettersson et al, 2018;Chang et al, 2020;Gul et al, 2020;Higuchi et al, 2020;Saltbak et al, 2020;AbuYahya et al, 2021;Kuusisto et al, 2022;Cuvalci et al, 2023).…”
Section: Ocena Kakovosti Pregleda In Opis Obdelave Podatkovunclassified
“…Pomemben pomen pri upoštevanju vodila »Ne oživljaj.« ima izobraževanje. V raziskavi Arzuaga et al (2018) so navedli, da medicinske sestre nimajo usposabljanja, sicer zanimanje za izobraževanje medicinske sestre kažejo (Mogadasian et al, 2014). Tudi raziskava, izvedena v Koreji, opozarja na pomen izobraževanja o upoštevanju volje, naprednih direktivah in pripravi na smrt (Woo & Kim, 2013).…”
Section: Demografski In Poklicni Dejavniki Medicinskih Sesterunclassified
See 1 more Smart Citation